Kajian Pemanfaatan Ruang Di Kawasan Keselamatan Operasi Penerbangan (KKOP) Bandar Udara Syukuran Aminuddin Amir Luwuk - Satria Hadinata; Irwan Prasetyo (Journal of Urban and Regional Development Studies, 2024)
Air transportation is a highly regulated mode of transport, particularly in terms of aviation safety. In an archipelagic country like Indonesia, air transportation is critical to the efficient and fair distribution of people, products, and services. Airports, as air transportation infrastructure, must be planned to ensure the safety of flight operations. Syukuran Aminuddin Amir Airport which supports the smooth flow of air transportation, also serves as a hub for regional mobility, impacting the land use planning and development in the airport area, especially concerning the Aviation Operation Safety Zone (KKOP). This study aims to explore the control measures for land use in the KKOP zone of Syukuran Aminuddin Amir Airport through land use analysis, identification of spatial land use characteristics, and risk potential mapping. The research findings indicate that there is a misuse of space in South Luwuk District. The four variables of land, water, or air usage requirements in the aviation operation area of Syukuran Aminuddin Amir Airport were all found to be non-compliant. To guarantee that these requirements are met in the KKOP, space usage control is conducted using tools such as zoning rules, permits, incentives and disincentives, and the implementation of punishments